University of Florida Potato Variety Trials Spotlight: ‘Fabula’: HS1294, rev. 2/2021 - Andrade, Mario H. M. L.; Mwatuwa, Rodrick Z.; Christensen, Christian T.; Solano, Pam; Zotarelli, Lincoln (EDIS, 2021)
‘Fabula’ is a potato variety that is commonly grown for the fresh potato market. The variety was selected from progeny of a cross between ‘Monalisa’ and ‘Hudson’. It was released in 2005 by D. Biedmond B.V. of the HZPC in the Netherlands. In Florida, ‘Fabula’ demonstrates good tuber characteristics and high yield superior to its commercial standard ‘LaChipper’. Tuber production and quality results are summarized from various trials conducted by the UF/IFAS Hastings Agricultural and Extension Center from 2001 to 2016. This is a minor revision with a new author added. Originally published 5/2017. https://edis.ifas.ufl.edu/hs1294